The Influence of Financial Inclusion and Internet Access on the Income of Poor Households - Hermawan, Wawan; Heriyaldi, Heriyaldi; Tjahjawandita, Ari (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2024)
West Java is the most populous province and has high levels of unemployment and poverty in Indonesia. This research analyzes the impact of financial inclusion and internet access on poor households' income in West Java. The study uses data from the March 2022 Social and Economic Survey by the Indonesian Central Bureau of Statistics and applies an econometric model. The analysis introduces a novel approach by categorizing poverty based on the poverty line, specifically targeting the lowest 20% and 40% of income-earning households. This method allows for a deeper understanding of financial inclusion and internet access's impact on these segments. The findings highlight that financial inclusion and internet access positively influence the income of poor households. Specifically, savings ownership increases the income of poor households. Access to credit positively affects income for the lowest 40% income bracket. However, internet access mainly influences sales and purchases within the 40% lowest income group, with limited use in purchasing activities.